Not-For-Profit Hospital Community Benefit: Hospital Prioritization of Opioid Use Disorder and Self-Pay Prices for Medications Prescribed for Opioid Use Disorder - Tatiane Santos; Jeanmarie Perrone; Berkeley Franz; Cory E. Cronin; Morgane C. Mouslim (Journal of Public Health Management & Practice, 2026)
ABSTRACT Context: Not-for-profit hospitals are required to provide community benefits (CB) in exchange for tax-exempt status, yet CB spending remains the predominant measure for assessing whether hospitals meet these obligations. Newly available hospital price transparency data offer an opportunity to evaluate whether hospitals' stated CB health priorities align with their financial practices. Objective: To examine whether not-for-profit hospitals that prioritize opioid use disorder (OUD) in CB planning are more likely to comply with price reporting for medications commonly prescribed for OUD treatment (OUD medications) and offer lower self-pay prices for OUD medications. Design: Mixed-methods cross-sectional study. Setting: United States not-for-profit hospitals. Participants: A nationally representative sample of 534 not-for-profit hospitals. Main Outcome Measure(s): Hospital compliance with OUD medication price reporting and median self-pay prices for medications commonly prescribed for OUD treatment. Results: Hospitals that prioritized OUD (n = 217; 40.6%) were located in counties with higher overdose mortality and greater levels of poor mental health. However, hospitals that prioritized OUD were neither significantly more likely to report self-pay prices for OUD medications nor more likely to offer lower self-pay prices for these medications. Overall, we found limited evidence that hospitals identifying OUD as a community health priority translated these stated priorities into pricing practices that may improve affordability for uninsured and underinsured patients. Conclusions: Identifying OUD as a community health priority may not be sufficient to ensure alignment between hospitals' stated commitments and financial practices affecting affordability and access to treatment. As calls for stronger hospital accountability grow, integrating price transparency data into CB oversight may help policymakers and hospital leaders strengthen accountability, transparency, and alignment between community health priorities and patient financial protections.